Efficient operation of the fourth Huaian pumping station in east route of South-to-North Water Diversion Project - Zhuan, Xiangtao; Zhang, Lei; Li, Wei; Yang, Fei (International journal of electrical power & energy systems, 2018)
•Operation scheduling of the pumps with blade adjustable is considered.•Computation-efficient algorithm is proposed and the global optimum is given.•Both the load shift and the efficient operation modes could result in cost reduction.•The algorithm can solve a class of nonlinear programming problems in other fields. The fourth Huaian pumping station is one of the second-stage pumping stations on the east route of the south-to-north water diversion project in China. The operation optimization problem of three pumps in the station is formulated to minimize the electricity cost while satisfying the flow demand. After analyzing the characteristics of the problem, a decomposition method is proposed to reduce the dimensionality of the optimization problem and thus the computation time. Simulation shows that the energy cost is reduced by 2.54% compared with the benchmark scheduling based on the proposed method. In comparison with the decomposition/aggregation-dynamic programming method and the dynamic programming with successive approximation method, the proposed algorithm can effectively save electricity costs for Huaian pumping station. The case study shows that the cost efficiency comes from two aspects: demand shift from the time intervals with a high electricity price to those with a low electricity price, and the operation mode with high energy efficiency. The former is subject to the pumps’ capacity and the daily demand. The larger the pumps’ capacity is, the more demand can be shifted and thus the lower the cost is. The latter is subject to the pumps’ characteristics and the pump heads. The larger the head is, the smaller the difference for energy efficiencies with different blade angles are, and the smaller the energy savings with the optimal operation are. When the demand is high for a given pump head, demand shifting is the main reason, while the second aspect is the main reason when the demand is low.